2019
DOI: 10.1186/s12929-019-0509-x
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin 2 from enterohemorrhagic Escherichia coli induces reactive glial cells and neurovascular disarrangements including edema and lipid peroxidation in the murine brain hippocampus

Abstract: BackgroundShiga toxin 2 from enterohemorrhagic Escherichia coli is the etiologic agent of bloody diarrhea, hemolytic uremic syndrome and derived encephalopathies that may result to death in patients. Being a Gram negative bacterium, lipopolysaccharide is also released. Particularly, the hippocampus has been found affected in patients intoxicated with Shiga toxin 2. In the current work, the deleterious effects of Shiga toxin 2 and lipopolysaccharide are investigated in detail in hippocampal cells for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…It has been showed that MG cells phagocytosis impairment worsens Alzheimer Disease pathology (Noda and Suzumura, 2012). In this regards, previous results have revealed cellular deleterious effects by STEC and LPS actions, the presence of Stx2 in abnormalphenotype neurons and neuronal damage which correlate with MG cells reactivity (Goldstein et al, 2007;Pinto et al, 2018;Berdasco et al, 2019). Former and present results build up one another showing that phagocytic MG cells correlated either with MG cells clearance function of Stx2-induced debris or Stx2 direct effect.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been showed that MG cells phagocytosis impairment worsens Alzheimer Disease pathology (Noda and Suzumura, 2012). In this regards, previous results have revealed cellular deleterious effects by STEC and LPS actions, the presence of Stx2 in abnormalphenotype neurons and neuronal damage which correlate with MG cells reactivity (Goldstein et al, 2007;Pinto et al, 2018;Berdasco et al, 2019). Former and present results build up one another showing that phagocytic MG cells correlated either with MG cells clearance function of Stx2-induced debris or Stx2 direct effect.…”
Section: Discussionsupporting
confidence: 70%
“…Microglial (MG) cells can be postulated as a central target in the harmful action caused by Stx2, as they belong to the monocyte-macrophage immune cell lineage (Xing et al, 2011). Along the same lines, our group has recently demonstrated in a translational murine model of HUS-derived encephalopathy that systemic sub lethal Stx2 induces MG cell reactivity in the striatum and the hippocampus (Pinto et al, 2018;Berdasco et al, 2019). We hypothesized that MG cells might play a pivotal role in the inflammatory effects of Stx2 observed in the brain and, thus, define the severity of encephalopathies in patients.…”
Section: Introductionmentioning
confidence: 96%
“…Although vascular and kidney involvement is prominent in human disease, in mice lethal disease occurs in the absence of gross pathologic changes to the vasculature or kidney. 39 However, lethal doses of Stx in mice are associated with neurologic changes, [39][40][41] and these could cause a decrease in feeding and drinking behaviors that result in weight loss. Neurologic complications also are seen in HUS, and are associated with more severe outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in memory index and depression-like behavior produced by the toxins in the nose-poke habituation task and the forced swimming test, respectively, may be related with damage in hippocampal neurons and correlate with the cognitive imbalance reported in patients [17]. Considering previous reports [911], Stx2 may damage hippocampal neurons in at least two ways: first, Stx2 binds to the canonical Gb3 receptor localized in CA1 hippocampal neurons; and, second, indirectly by an inflammatory process with MG playing a fundamental role [10]. Indeed, we have recently reported in an in vitro model that Stx2 is up-taken by MG through its receptor Gb3, which produces an increase in MG metabolism, phagocytic capacity and pro-inflammatory cytokine release [29].…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, the M2 profile is responsible for the secretion of anti-inflammatory cytokines such as IL-10 [3234]. In addition, secretory ameboid MG morphology may also be an important oxidative source of reactive oxygen species (ROS) and nitric oxide (NO) radical derived products [35], as we have previously shown in the current model of Stx2-produced encephalopathy [11].…”
Section: Discussionmentioning
confidence: 98%